THE ROLE OF SELF-STRENGTH ABILITIES IN INCREASING THE LEVEL OF PHYSICAL FITNESS OF STUDENTS OF MILITARY TRAINING CENTERS - Ignatov, A.A.; Shilko, V.G. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to identify the effectiveness of the use of training cycles in the process of physical exercises aimed at developing self-strength qualities, and to assess their impact on the level of physical fitness of students of military training centers in general. Methods and structure of the study. To achieve this goal, a six-month pedagogical experiment was conducted on the basis of the military training center at the National Research Tomsk State University, in which 20 4th-year students (male, aged 21-22 years) took part in the training programs frame officers. The experimental and control groups of 10 people each were formed from the number of subjects. The experimental group (EG) was engaged according to the developed training plan containing cycles aimed at developing self-strength qualities. The control group (CG) underwent complex training sessions in gymnastics and athletic training, in which low-intensity exercises with own body weight and non-limiting weights were used. Results and conclusions. On the basis of the results of the pedagogical experiment, it was proved that the construction of the educational and training process, taking into account the cyclical nature of physical activity, aimed at developing self-strength qualities, contributes to the formation of a higher level of physical fitness of students of military training centers in general.